Complement 5a stimulates hepatic stellate cells in vitro, and is increased in the plasma of patients with chronic hepatitis B. Issue 3 (5th February 2013) - Xu, Ruonan; Lin, Fang; He, Jin; Jin, Lei; Zhang, Ji‐yuan; Fu, Junliang; Liu, Honghong; Wang, Siyu; Zhang, Zheng; Wang, Fu‐Sheng
Summary Complement 5a (C5a) is a critical modulator of liver immunity. In this study, we investigated the role of C5a and its receptor in liver fibrosis in patients with hepatitis B virus infection. We found that plasma C5a concentration was significantly increased in patients with chronic hepatitis B, particularly in those patients with higher grade and stage scores. Further analysis indicated that the increased C5a concentration was positively correlated with clinical parameters reflecting liver fibrosis severity, including type IV collagen and procollagen type III N‐terminal peptide. Our in vitro data indicated that the C5a receptor is highly expressed in hepatic stellate cells (HSCs). Addition of C5a significantly activated HSCs and up‐regulated α‐smooth muscle actin, hyaluronic acid and type IV collagen expression. Also, addition of C5a could inhibit the spontaneous and soluble tumour necrosis factor‐related apoptosis‐inducing ligand‐induced apoptosis of HSCs. These findings highlight the potential role of C5a in the regulation of liver fibrosis.